Design and Comparison of Two Control Strategies for Voltage-sag Compensation using Dynamic Voltage Restorers - Torres, A. P.; Roncero-Sanchez, P.; del Toro Garcia, X.; Feliu, V. (Elektronika ir Elektrotechnika, 2013)
The Dynamic Voltage Restorer (DVR) is one of the most frequently used devices for voltage-sag compensation. This work explains the design procedure and comparison of two different control strategies for the compensation of balanced and imbalanced voltage sags by using a DVR. The two strategies considered are the widely-used proportional-integral (PI) controller and a new approach based on the generalized proportional-integral (GPI) controller. Both control schemes are implemented in a synchronous reference frame (SRF) and use a feedforward term to improve the time response. The simulations in PSCAD/EMTDC show the performance of both control strategies for several voltage sags and for grid-frequency deviations. The obtained results show that the SRF-GPI approach is superior. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.4553